Control fisicoquímico de amoxicilina 875 mg + ácido clavulánico 125 mg tableta recubierta realizado en un Laboratorio Farmacéutico Nacional, 2016-2017 - Miranda Lopez, Carlos Ausberto (2018)
This report of pre-professional practices entitled: Physico-chemical control of amoxicillin 875 mg + clavulanic acid 125 mg coated tablet made in a National Pharmaceutical Laboratory, 2016-2017, was carried out with the objective of determining whether physicochemical control trials of amoxicillin 875 mg + clavulanic acid 125 mg coated tablet from a national pharmaceutical laboratory, meet the specifications according to their analytical technique. The sample consisted of 60 tablets of five batches. The physicochemical control of the samples was carried out according to the analytical technique of the laboratory during the pre-professional practices, which includes own methodologies, from the Pharmacopeia of the United States of America (USP 39-NF 31) and the British Pharmacopoeia (BP 2016) . The tests carried out were: description, uniformity of weight, water-Karl Fischer, identification and measurement by ultrahigh-resolution liquid chromatography (UHPLC), uniformity of dosage units and dissolution. It is concluded that amoxicillin 875 mg + clavulanic acid 125 mg coated tablet meets the specifications established in the analytical technique